Human Capital Development and Growth in Africa: Does Youth Unemployment Matter? - Benedict, Olanipekun Dayo (Asian Journal of Economic Modelling, 2020)
The rates of youth unemployment and low human capital development in Africa have been worrisome. This study empirically investigated the role that youth unemployment played in the relationship between human capital and growth in Africa. The effects of both male and female youth unemployment on growth were examined. A system generalized method of moment (GMM) was used to estimate the model employed in the study. It was found that youth unemployment had resulted to a detrimental effect on growth in Africa in diverse ways. While, male youth unemployment was found to have a negative and statistically significant effect on growth, female youth unemployment shows no statistically significant effect on GDP per capita in Africa. Among the human capital development indices used in the regression, only primary school enrollment was found to have a positive and statistically significant effect on GDP per capita. Secondary and tertiary enrollments were found to be statistically insignificant. Appropriate policies geared towards job creation for the youths and human capital development would reduce the detrimental effect of youth unemployment and low human capacity building on long run growth.